Ultrasonic Time-Frequency Response Characteristics for Damage Evolution of Back-Filling Concrete under Staged Loading Conditions - Xicai Gao; Xichen Zhang; Cheng Zhao; Huan Xia; Shuai Liu; Tengfei Ma; Jianhui Yin; Kai Fan (Advances in Materials Science and Engineering)
Under the influence of repeated mining disturbance, the back-filling body for the gob-side entry retaining may experience a reduction in the bearing capacity or even failure, complicating the control of surrounding rock stability in coal mines. This study employs an electro-hydraulic three-axis servo testing machine and an ultrasonic detection system to study damage evolution and the precursor instability response behavior of the back-filling concrete of the gob-side entry retaining. Specifically, we conduct staged loading experiments on the specimens of back-filling concrete. By analyzing the characteristic stress of the concrete specimens and the ultrasonic time-frequency response characteristics, we explore the damage evolution and bearing capacity deterioration process. Results show that under staged loading conditions, the concrete specimens underwent a differential change process from nonuniform to uniform deformation, to localized deformation, and finally to failure. The velocity of the ultrasonic wave of the loaded concrete specimens first increased, then decreased with increasing stress, and the macroscopic deformation characteristics were consistent with damage development and evolution, showing clear stage-specific characteristics. The ultrasonic time-frequency response characteristics of the loading process characterized damage accumulation in the concrete specimens, loading state variation, and the deterioration of load-bearing capacity in great detail. During the staged loading process, the attenuation coefficient was positively correlated to bearing capacity, and the coefficient of variation (CV) of the dominant frequency was inversely proportional to the degree of crack development. Compared with the ultrasonic wave velocity, the time-frequency response characteristics were more sensitive to damage evolution. In summary, our findings provide an experimental basis for long-term stability monitoring and evaluation of the back-filling body for gob-side entry retaining in coal mines.